2021
DOI: 10.1002/ajpa.24424
|View full text |Cite
|
Sign up to set email alerts
|

A biological approach to adult sex differences in skeletal indicators of childhood stress

Abstract: Objectives: In previous work examining the etiology of cribra orbitalia (CO) and porotic hyperostosis (PH) in a contemporary juvenile mortality sample, we noted that males had higher odds of having CO lesions than females. Here, we examine potential reasons for this pattern in greater detail. Four non-mutually exclusive mechanisms could explain the observed sex differences: (1) sex-biased mortality; (2) sexual dimorphism in immune responses; (3) sexual dimorphism in bone turnover; or (4) sexual dimorphism in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 149 publications
(182 reference statements)
2
19
0
Order By: Relevance
“…Patterns of morbidity and mortality associated with PSL, particularly in non‐adults, may be absent from sex estimate data in archaeological contexts (McFadden & Oxenham, 2020), making it essential to analyze identified skeletal samples (e.g., O'Donnell et al, 2021). In this research, the appearance of porous lesions occurred independently of the biological sex, contrary to what was reported by O'Donnell et al (2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patterns of morbidity and mortality associated with PSL, particularly in non‐adults, may be absent from sex estimate data in archaeological contexts (McFadden & Oxenham, 2020), making it essential to analyze identified skeletal samples (e.g., O'Donnell et al, 2021). In this research, the appearance of porous lesions occurred independently of the biological sex, contrary to what was reported by O'Donnell et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is intended to test the following predictions: Non‐adult males are more affected by PSL than females because they have increased osteoblastic activity, whereas non‐adult females maintain yellow marrow for longer (O'Donnell et al, 2021). Younger individuals present higher frequencies of PSL because anemia developed after childhood is not expected to affect bone as severely as in younger ages (Stuart‐Macadam, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The documentation associated with the individuals' health and death records indicated that the individuals likely had to be sick for several weeks at least to develop detectable CO or PH. However, no mortality bias according to sex or age was established for the prevalence of either lesion (O'Donnell et al, 2022). O'Donnell and colleagues bring invaluable information on the prevalence and etiology of CO and PH, which was previously lacking to validate the use of these lesions as non‐specific skeletal markers of childhood stress or disease in both contemporary and past populations.…”
Section: Introductionmentioning
confidence: 99%
“…The documentation associated with the individuals' health and death records indicated that the individuals likely had to be sick for several weeks at least to develop detectable CO or PH. However, no mortality bias according to sex or age was established for the prevalence of either lesion (O'Donnell et al, 2022).…”
mentioning
confidence: 96%